Analysis of the Ability Level of MSME Entrepreneurs in Accessing Sharia Banking Financing at Bank Syariah Indonesia KC Lubuk Pakam - Fili, Nada Sausan Adha; Anggraini, Tuti; Daulay, Aqwa Naser (SAFE-Network, 2025)
SMEs play an important role in the national economy, but their access to financing from financial institutions, especially Islamic banking, still faces various obstacles. The low level of financial inclusivity, the complexity of administrative procedures, and limited infrastructure are the main obstacles. This study aims to describe and analyze the level of capability of MSME entrepreneurs in accessing sharia banking financing at Bank Syariah Indonesia (BSI). The approach used is descriptive qualitative with a survey method involving 20 respondents selected through purposive sampling. Data were collected through closed questionnaires with a five-point Likert scale and analyzed descriptively. The research results indicate that although BSI provides various Sharia financing products, there are still obstacles faced by MSME actors, such as a lack of understanding of the products, complex administrative procedures, and limited infrastructure and services. The dominance of female respondents also indicates the need for special attention to improving financial inclusivity for women in business management. This study recommends enhancing financial education, simplifying procedures, and strengthening infrastructure and services so that access to Sharia financing for MSMEs can be more inclusive and sustainable.